Being Empathetic to Preschool Children: Redefining the Design Process of Digital Platform to Support Early Childhood Development in Indonesia - Khafidlotun Muslikhah; Gadis Febriani (Jurnal Desain Produk Nasional, 2026)
The widespread use of digital applications to preschoolers has created two opposing perspectives. Health experts often warn parents about the negative effects of screen time, while some IT practitioners and even education practitioners highlight the potential of digital platforms for people including preschoolers' development. This paper explores the possibility of creating a digital platform that bridges the two opposing perspectives by developing the conceptof digital platform which could give meaningful and healthy screen time for children in Indonesia. This exploration begins by studying the landscape of digital platforms as learning media for preschoolers using the PRISMA framework. Then the results of the exploration of the landscape are compared with digital platforms that have been proven to have a positive impact on preschool children. From the results of the comparative analysis, the author recommends the importance of empathizing with preschool children, especially regarding their needs and abilities. To support the empathy process, the author recommends a design process with some research methods and cross-disciplinary collaboration with child education experts, so that designer and developer can truly propose a digital platform that is meaningful and beneficial for the emotional and cognitive development of preschool children.